324 Total Knee Arthroplasty in Haemophilia Patients: A Systematic Review and Meta-Analysis of Long-Term Survivorship, Functional Outcomes and Complications. (19th August 2022) - Fu, H; Peacock, C; Wang, C; Kader, D; Asopa, V; Sochart, D
Abstract: Aim: End-stage arthropathy is a well-known complication of haemophilia, with recurrent haemarthroses leading to joint destruction, deformity, pain, and stiffness. In the knee, this is often treated with total knee arthroplasty (TKA), which can be more challenging in patients with haemophilia (PwH) and associated with poorer outcomes. We conducted a systematic literature review and meta-analysis to determine implant survivorship, functional outcomes, and complication rates. Method: A systematic review was conducted using MEDLINE, EMBASE, and PubMed for studies reporting TKA outcomes with Kaplan-Meier survivorship in PwH (PROSPERO registered). Meta-analysis was performed for survivorship and outcomes, and the results were compared to outcomes from the National Joint Registry (NJR). Results: 19 studies, totalling 1187 TKAs (average age 39 years) were reviewed. In PwH, implant survivorship at 5, 10, and 15 years was 94%, 86%, and 76% respectively, whereas NJR reported survivorship for males <55 years was 94%, 90%, and 86%. Survivorship generally improved over the time period studied (1973–2017) but was inversely correlated with HIV infection (common in PwH). Range of motion improved by 10–20° post-operatively, and there were large improvements in Patient Reported Outcome Measures (PROMS). The prosthetic joint infection rate (PJI) was 6% compared to 0.5–1% in non-PwH, but the reporting of other complications, especially haematological, was inconsistent. Conclusions: TKA in PwH has similar 5-year survivorship to non-PwH, but a six-fold higher infection rate. There were marked improvements in range of motion and PROMS, but complications were poorly reported. There remains a need for larger, long-term studies with standardised reporting.